PARTICIPATORY OBSERVATION IN MADRASAH ALIYAH AS A REFERENCE OF LEARNING MODELS IN ERA 4.0 - Eva Iryani, M.Sobri, Friscilla (EDU-RILIGIA: Jurnal Ilmu Pendidikan Islam dan Keagamaan, 2020)
Abstrack: National education aims to develop the potential of students so that they become individuals who have faith and piety to God Almighty, who have a noble attitude, who are healthy, enlightened, capable, creative, independent, and who can become democratic and responsible citizens. With such heavy objectives, all learning activities and processes must support these goals. Campus as one of the educational institutions that have the responsibility to support goals is required and given the task to carry out the Tridarma of Higher Education. And the outputs of Tridarma in the form of research and service must be based on these goals and integrative intelligence. Community service with the socialization of participatory observation learning model was carried out with Madrasah Aliyah 2 Jambi City as a collaborative partner. With the aim that teachers in these schools can actively use innovative and renewable learning models. And further, the socialization efforts support the Ministry of Education and Culture jargon with the concept of free learning. In supporting these efforts to improve, it must be supported by a set of approaches and learning models that can help and reconstruct and realize this large tagline. One of them is through an approach that seeks to involve and optimize all instruments and learning tools that support the independence of the educational process. One such effort is through a participatory observation clarification model.Keywords: integrative intelligence, Free Learning and observation